Ginkgo Biloba Protects Against Carbon Tetrachloride Induced Liver Injury in Albino Rat - Maria Kazi, Shuja Anwer Ka; Syed All Akbar Shah (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To investigate hepatoprotective effect of Ginkgo biloba aqueous extract (GkB) against carbon tetrachloride (CC14) induced liver injury in albino rat model. Study design: Experimental/Analytical study Place and Duration: Animal House, Isra University Hyderabad campus, from March to July 2014. Subjects and Methods; Forty five albino rats were divided into three groups; Group 1. controls received 0.9% isotonic saline, Group II. received CO, orally (1.9mg/kg) mixed in olive oil, and Group III. received the CC14+ GkB. Blood samples were collected for liver biochemical assays. The animals were sacrificed, liver tissue, after fixation in 4% formaldehyde, was embedded in paraffin. Tissue sections of 5/4 thickness were subjected to haematoxylin and eosin staining and were assessed by light microscopy. The data was analyzed on Statistix 8.1 using one-way analysis of variance using post Hoc testing. A p-value of= 0.05 was taken statistically significant. Results: The liver biochemical and histological findings reveal statistically significant differences among the controls, CC1, and CC14+ GkB groups (p=0.0001). Liver enzymes and histology were deranged significantly in CC1, group compared to controls and CC1+ GkB group ()=0.0001 ).The CCI4± GkB group showed lesser rise in liver enzymes and derangement of liver histology compared to CO, group (p=0.001 ). The histological findings of congestion, inflammatory cell infiltrate, vacuolar degeneration and necrosis were found more pronounced in CCI, group. Conclusion: The Ginkgo biloba protects against oxidative damages caused by carbon tetrachloride induced liver injury in albino rat.